প্রত্যক্ষ নয়নে: Zainul Abedin Art Museum Mymensingh, Bangladesh - Hasan, Md. Rakibul (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture, 2022.